PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN DI J4 HOTEL LEGIAN KUTA BALI - Efifania Diah Pramesti; Made Yudi Darmita; Luh Gede Putri Kusuma Pekerti (Journal Research of Management, 2022)
This study aims to determine the effect of leadership and communication on employee job satisfaction at J4 Hotel Legian Kuta Bali. This study is a quantitative study that describes and explains how the influence of leadership and communication on employee job satisfaction at J4 Hotel Legian Kuta Bali. The population used was 45 employees who were also used as research samples, namely 45 respondents. The test of this research instrument uses validity and reliability tests. The data analysis technique used is multiple linear regression, classical assumption test, T test and F test and standardized coefficient beta. The results show that (1) leadership has a positive effect on employee job satisfaction at J4 Hotel Legian Kuta Bali with a value of 0.535 with a significance of 0.001 <0.05, (2) communication has a positive effect on employee job satisfaction at J4 Hotel Legian Kuta Bali with a value of of 0.450 with a significance of 0.003 < 0.05, (3) leadership and communication simultaneously affect employee job satisfaction at J4 Hotel Legian Kuta Bali with a calculated F value of 22.365 > F table of 3.22 and a significance of 0.000 < 0.05 , (4) leadership has a dominant influence on employee job satisfaction at J4 Hotel Legian Kuta Bali with a standardized coefficient beta value of 0.454 > standardized coefficient beta communication of 0.380.